Verification of micro-scale photogrammetry for smooth three-dimensional object measurement - Sims-Waterhouse, Danny; Piano, Samanta; Leach, Richard K. (IOP Publishing, 2017)
By using sub-millimetre laser speckle pattern projection we show that photogrammetry systems are able to measure smooth three-dimensional objects with surface height deviations less than 1 μm. The projection of laser speckle patterns allows correspondences on the surface of smooth spheres to be found, and as a result, verification artefacts with low surface height deviations were measured. A combination of VDI/VDE and ISO standards were also utilised to provide a complete verification method, and determine the quality parameters for the system under test. Using the proposed method applied to a photogrammetry system, a 5 mm radius sphere was measured with an expanded uncertainty of 8.5 μm for sizing errors, and 16.6 μm for form errors with a 95 % confidence interval. Sphere spacing lengths between 6 mm and 10 mm were also measured by the photogrammetry system, and were found to have expanded uncertainties of around 20 μm with a 95 % confidence interval.